Firm location decisions, regional grants and agglomeration externalities. - Devereux, M; Griffith, R; Simpson, H (Elsevier, 2007)
We examine whether discretionary government grants influence where domestic and multinational firms locate new plants, and how the presence of agglomeration externalities interacts with these policy instruments. We find that a region's existing industrial structure has an effect on the location of new entrants. Grants do have a small effect in attracting plants to specific geographic areas, but importantly, we find that firms are less responsive to government subsidies in areas where there are fewer existing plants in their industry. This suggests that these subsidies are less effective in influencing firms' location decisions in the face of countervailing co-location benefits.